Metal and Non-Metal Modified Titania: the Effect of Phase Composition and Surface Area on Photocatalytic Activity - Boštjan Žener; Lev Matoh; Martin Reli; Andrijana Sever Škapin; Romana Cerc Korošec (Acta Chimica Slovenica, 2022)
The application of TiO2 photocatalysis in various environmental fields has been extensively studied in the last decades due to its ability to induce the degradation of adsorbed organic pollutants. In the present work, TiO2 powders doped and co-doped with sulfur and nitrogen and modified with platinum were prepared by particulate sol-gel synthesis. PXRD measurements revealed that the replacement of HCl with H2SO4 during synthesis reduced the size of the crystallites from ~ 30 nm to ~20 nm, increasing the surface area from ~44 m2/g to ~80 m2/g. This is consistent with the photocatalytic activity of the samples and the measured photocurrent behavior of the photocatalysts. The results showed that the properties of the powders (i.e., surface area, crystallite size, photocurrent behavior) depend strongly not only on the type but also on the amount of acid and dopants used in the synthesis. Doping, co-doping and modification of TiO2 samples with nitrogen, sulfur and platinum increased their photocatalytic activity up to 6 times.